Determination of Pharmacological and Therapeutic Potential of Cissus quadrangularis L. - Sheik Abdulla Shahul Hameed; Renuka Saravanan; Sivakumar Ramalingam; Sampath Kumar Palanisamy (Current Aspects in Pharmaceutical Research and Development Vol. 6, 2021)
The present study carried out to determine the Pharmacological and therapeutic potential of Cissus quadrangularis L. Cissus quadrangularis(CQ) Linn., commonly known as Veldt Grape, Winged Tree-bine or Devil’s Backbone, is a plant native to India and Sri Lanka and indigenous to Asia and Africa. Numerous studies support the development of new treatments in oncology to be added to the traditional protocols to increase the effectiveness of available treatments, reducing side effect profile, and the patients’ quality of life. Chemotherapy- induced side effects depend on various variables such as the drug employed, its dosage, and treatment duration. These side effects include pain, fatigue, throat and mouth sores, diarrhoea, nausea, vomiting, constipation, and blood disorders. Side effects affecting the nervous system are commonly experienced with chemotherapy and include cognitive dysfunction, headache, dizziness, vision loss and vision disturbances such as blurred or double vision, changes in learning and memory, sexual dysfunction, ataxia, and peripheral neuropathy